(untitled) (Fiep Bulletin - online, 2011)
The central concern of this exploratory qualitative claims in collecting and analyzing the opinion of some expert teachers and class teachers who instruct the 1st to 4th grade education, so as coordinators and school principals. The goal is to evaluate the action of specialist teachers in these series. 8 teachers were interviewed experts in physical education, 8 classroom teachers, 6 coordinators and directors of 6 schools in the state public school located in the south. The interviews did not reveal the quality classes taught by specialists. In so far have taught classes only for students in the later series of elementary school these professionals had difficulty in the courses for the first grades of elementary school. The classroom teachers, coordinators and directors interviewed said the importance of having a professional school health, however, show that these classes are being offered with quality. In this sense, the data obtained from the experts interviewed pointed to the need for refresher courses in continuing education and a more integrated with the school staff so that they can take with quality, physical education classes in early grades of education fundamental, so that they fulfill their true purpose, main point that will differentiate the lessons taught by classroom teachers.